Intelligent buildings : design, management and operation - Clements-Croome, Derek (ICE Publishing, 2013)
Intelligent buildings provide stimulating environments for people to work and live in. This book brings together a body of the latest knowledge about design, management, technology and sustainability set against the background of developments in the cultural landscapes, which affect those living and working in buildings.
Erratum sheet in pocket.
Keywords: Intelligent buildings.; elektronické knihy; electronic books